Republic of Poland : Insurance Core Principles, Detailed Assessment of Observance - International Monetary Fund; World Bank (Washington, DC, 2014)
This assessment is focused on the Komisja Nadzoru Finansowego (KNF, the financial supervisory commission), specifically on its supervision of the insurance sector. KNF has responsibility for licensing and supervising all players in the insurance market that is insurance companies, insurance brokers, agents, loss adjusters, reinsurance companies, and reinsurance brokers. The assessment was performed using the 2007 version of the insurance core principles (ICPs) issued by the International Association of Insurance Supervisors (IAIS) and the methodology described by the IAIS. Each ICP is rated in terms of the level of observance as follows: observed - whenever all the standards are considered to be observed or when all the standards are observed except for a number that are considered not applicable; not applicable - when the standards are considered to be not applicable; largely observed - where only minor shortcomings exist, which do not raise any concerns about the authorities' ability to achieve full observance; partly observed - where, despite progress, the shortcomings are sufficient to raise doubts about the authorities' ability to achieve observance; and not observed - where no substantive progress toward observance has been achieved.